USE OF THEORY OF DEVELOPMENT AND SPACE REGIONAL ECONOMIC ORGANIZATIONS FOR ITS REFORM: EXPERIENCE OF FOREIGN COUNTRIES AND THE EXTERNAL USSR - Zakharchenko, V.I. (The actual problems of regional economy development, 2019)
The article is aimed at studying the experience of foreign countries and the former USSR in terms of reforming the economy of the regions, using theories of their development and spatial organization. To this end, the corresponding theories are grouped according to their belonging to the main schools of economic thought and practical orientation. Also, the experience of their positive application is revealed. Thus, theories of the first group, which are based on classical political economy, marginalism and neoclassicalism, are oriented towards the improvement of the spatial organization of the economy (theories of production placement and the spatial organization of the economy), the greatest application was found in Germany and the former USSR. Theories of the second group (planned economic and Keynesian type), envisaging large-scale state aid to backward regions, such as the theory of state regulation of the development of regions, were widely practiced in the USSR and the United States. Theories of the third group (institutional direction), which are aimed primarily at interregional redistribution of economic growth (regional science, "growth poles", clusters, etc.), were used in most countries of the world, but their experience in France, Italy and Finland. Theories of the fourth group (based on the neoclassical synthesis), which envisage the balanced use of the resource potential of the regions (primarily the theory of sustainable self-development of the regions), have become widespread in the EU countries and may therefore become particularly popular in Ukraine in connection with its Euro-integration aspirations. It is the latter group of theories that should become the "core" of the ensemble of theories, which it is advisable to rely on in the process of reforming the economy of the regions of Ukraine.